ANALYSIS OF THE USE ELECTRONIC BOOKS (E-BOOKS) BY USERS IN PUBIC LIBRARY - Pasaribu, Kiki Ramadayanti; Rohani, Laila (Academic Solution Publisher, 2023)
The research method used is a qualitative method with a descriptive approach that uses interviews to describe the data obtained by researchers directly, to obtain a clear and detailed picture of how the use of electronic books (e-books) by users at the library and archives office of Labuhan Batu district. The data collection techniques used in this study were interviews and observations. Furthermore, the researchers conducted interviews with 5 informants, namely the users at the Library and Archives Service of Labuhan Batu Regency. The results of this study indicate that the use of electronic books (e-books) by users is that they use electronic books to get references and their information needs such as doing paper assignments given by lecturers. Obstacles experienced by users, especially in unstable networks, lack of collections of books in the e-book, and according to them the obstacles are the lack of experts in the field of e-books so that e-books are not optimal and lack of socialization to users so that some users do not understand in browsing the e-book.